Seven years of the field epidemiology training programme (FETP) at Chennai, Tamil Nadu, India: an internal evaluation - Bhatnagar Tarun; Gupte Mohan D; Hutin Yvan J; Kaur Prabhdeep; Kumaraswami Vasanthapuram; Manickam Ponnaiah; Murhekar Manoj; Ramachandran Vidya; Ramakrishnan Ramachandran (BMC, 2012)
Abstract Background During 2001-2007, the National Institute of Epidemiology (NIE), Chennai, Tamil Nadu, India admitted 80 trainees in its two-year Field Epidemiology Training Programme (FETP). We evaluated the first seven years of the programme to identify strengths and weaknesses. Methods We identified core components of the programme and broke them down into input, process, output and outcome. We developed critical indicators to reflect the logic model. We reviewed documents including fieldwork reports, abstracts listed in proceedings and papers published in Medline-indexed journals. We conducted an anonymous online survey of the graduates to collect information on self-perceived competencies, learning activities, field assignments, supervision, curriculum, relevance to career goals, strengths and weaknesses. Results Of the 80 students recruited during 2001-2007, 69 (86%) acquired seven core competencies (epidemiology, surveillance, outbreaks, research, human subjects protection, communication and management) and graduated through completion of at least six field assignments. The faculty-to-student ratio ranged between 0.4 and 0.12 (expected: 0.25). The curriculum was continuously adapted with all resources available on-line. Fieldwork led to the production of 158 scientific communications presented at international meetings and to 29 manuscripts accepted in indexed, peer-reviewed journals. The online survey showed that while most graduates acquired competencies, unmet needs persisted in laboratory sciences, data analysis tools and faculty-to-student ratio. Conclusions NIE adapted the international FETP model to India. However, further efforts are required to scale up the programme and to develop career tracks for field epidemiologists in the country.